Pengaruh Latihan Squat Jump dan Bodyweight Squat Terhadap Kekuatan Otot Tungkai Pada Atlet Wushu Taolu di Kabupaten Kudus - Ihsani, Ilham; Aji, Tri (UNIB Press, 2025)
This study aims to determine the effect of squat jump and bodyweight squat training on leg muscle strength of Kudus Regency Wushu athletes. Quantitative data from a quasi-experimental design are used in this study. The sample for this study included 16 individuals between the ages of 15 and 20 who were male and female Wushu Taolu practitioners in the Kudus Regency. The research instrument used pretest-posttest data collection with the vertical jump test. Normality tests, homogeneity tests, and t-test hypothesis tests are all included in data analysis procedures. The comes about appeared that there was a noteworthy impact of squat hop and bodyweight squat preparing on leg muscle quality of Kudus Regency Wushu Taolu athletes. The percentage increase in squat jump training is 15.31%, while bodyweight squat training has a percentage increase of 14.69%. This shows that squat jump training and bodyweight training both have a significant effect on increasing leg muscle strength.